STUDI KASUS GANGGUAN ENURESIS PADA SEORANG MAHASISWI DI YOGYAKARTA (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2009)
The objective of the study is to know the problems that back ground enuresis interference happen to a college student in Yogyakarta. The test-taker is subject who does certain activity / prominent subject of the study, that is the subject who undergoes enuresis interference that give some exact and clear information. The number of subject of the study is one (N:1). The data collected from interview, observation, psychological test (DAM, HTP, Baum) and self monitoring as the method of collecting data. The result of the study shows that the major factor of the subject who undergo enuresis interference is because of less harmonious relationship with family. The overwhelming problem experienced by the subject made her feel depperessed. The pressure influences hypothalamus work, otonomical nurve system, and adrenal cortical system, but since of the pressure takes chemically, and subject could not overcome it so it attack the weakest part of the body, that is ureter, so enuresis happens